Linguistic (human) rights and their violations in Transcarpathia (1944–2022) - Csernicskó István; Черничко Степан; Csernicsko Istvan (Méry Ratio Publishing, 2022)
Abstract. What are linguistic rights? Since 1948 the Universal Declaration of Human Rights has summed up all those universal human rights that belong to all people(regardless of gender, age, regligion, mother tongue, color or financial situation). This extremely important document, however, practically says nothing about what rights are linked to language use, thus it does not shed light on what exactly universal linguistic (human) rights are.
Keywords: Transcarpathia; Linguistic Right; 1944-2022